Bibliotherapy in Sri Lankan Higher Education System: Implications for University libraries - Arulanantham, S.; Navaneethakrishnan, S. (Sri Lanka Library Association, 2014)
Bibliotherapy involves the systematic use of books to help people cope with mental, physical, emotional, or social problems. It has been widely identified as an approach that holds great assurance in helping librarians to deal with emotional, behavioral and social concerns of various groups of people. Bibliotherapy as a term coined by Samuel Crothers in 1916 is deriving from two Greek words biblio meaning "book" and therapia meaning "healing". Many educators and adults have resorted to bibliotheraphy to help individuals and groups deal with normal and emotional problems they encounter (Rubin, 1978). In this post war era, knowledge capital of Sri Lanka mainly depends on the human capital of higher education system. Undergraduate students are identified as core group of sustainable human capital. Strategies to improve their intellectual power will encourage the development of this nation. As such, it is realised that this is the opportune time for the library professionals to study the current situation of Sri Lankan higher education with regard to the social needs as well as health care necessities of the undergraduates and to identify the role of the university libraries in fulfilling these obligations. The principal objective of this research is to identify the stimulating reasons to the provision of bibliotheraphy for undergraduate students in Sri Lanka. Further, this study insists the role and responsibility of university libraries in the provision of bibliotheraphy as a service in Sri Lanka. Descriptive method is used in this study. Based on descriptive analytical survey of literature on higher educational reforms and social problems related to undergraduates in Sri Lanka, this study emphasizes significant and basic need of bibliotheraphy in university libraries. Findings of this study shows there have been several studies conducted on the disability and disorder of Sri Lankan undergraduates. Blind and disabled students have a provision for university entrance. Other than them, Universities have disable undergraduates due to the natural and man made disasters. Ragging and violence have become inseparable activities among the undergraduates (Darshani Wimalasuriya 2013). There are several contributory factors for the onset of emotional disorders among undergraduate students (Athukorala 1995). Another study confirmed the high frequency of emotional disorders among entrants to universities in Sri Lanka (Kathriarachchi Ariyaratne Jiffry 2001). Library Services to People with Special Needs (LSN) developed by IFLA insists involvement of health sector on library service to physically and developmentally disabled readers. Bibliotherapy service could be implemented for the undergraduate students in university libraries with the support of Ministry of health, Sri Lanka. As UNESCO stipulates that libraries have an obligation to serve to readers with special needs, university libraries could play vital role in changing the attitude of physically, developmentally disabled undergraduate students. Awareness also could be created by arranging special corners bibliotherapy corners in university libraries to ensure the information rights of undergraduate students. Policy decision could be made at national level for bibliotheraphy service provision to undergraduate students in university libraries under the direction of SCOLIS in collaboration with the ULA of Sri Lanka, based on international recommendations and standards.
Keywords: Bibliotherapy; Higher education; Sri Lanka